Rasionalisasi Ekonomi Politik Lingkungan dalam EU-Japan Economic Partnership Agreement (EU-JEPA) - Rafsyanjani Mohammad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This research aims to explain the rationale behind the inclusion of â€œParis Agreement clauseâ€ in the EU-Japan Economic Partnership Agreement (EU-JEPA) which has been in force since 2019. Especially this research will analyze various political economy factors from EUâ€™s perspective which influence the inclusion of such clause. The author uses Environmental Political Economy â€œInstitutionalistâ€ perspective which argues that conflictual relationship between trade and environment issues can be resolved through institutionalism approach which emphasizes the existence of international agreements, regulations, and governances in bilateral, regional, and global levels. Furthermore, this article discovers that such political economy factors can be found from economy benefits potential offered by trade liberalization and EUâ€™s participation in Paris Agreement global climate change governance. These two factors are closely interrelated and together determine EUâ€™s rationale in the inclusion of Paris Agreement clause into this trade agreement with Japan.